Analyzing the impact of psychological capital and work pressure on employee job engagement and safety behavior - Saleem, Muhammad Shoaib; Isha, Ahmad Shahrul Nizam Bin; Benson, Chizubem; Awan, Maheen Iqbal; Naji, Gehad Mohammed Ahmed; Yusop, Yuzana Binti (Frontiers in Public Health, 2022)
Introduction Buildings and infrastructure are the primary focus of the construction industry, which also includes related activities such as design, planning, demolition, renovation, maintenance, and repair. Safety performance is crucial to the industry's ability to work effectively in spite of hazardous conditions on the job site during any given project. Improving construction workers' safety performance in Malaysia requires an in-depth examination of the interplay between workers' psychological capital, work pressure, employee engagement, and safety participation. Methods Administrative and field workers from different divisions across Malaysia's six regions were randomly sampled to collect data for this study. The workers were given a total of 500 questionnaires, of which 345 were returned to the team of researchers. Based on the data analysis, there is an effective interaction between the factors tested toward safety performance. Results According to findings, psychological capital positively and significantly affected workers' work engagement. Also, work engagement greatly impacted both workers' safety performance outcomes. Also, as expected, worker pressure significantly and negatively affected workers' safety performance. Discussion Insights gained from this research have helped us better organize work and involve employees in safety activities/policies to boost workplace safety performance. The study also suggested that firms should reduce their employees' workloads because doing so would not lower their Psychological Capital but would instead fortify them to better carry out their duties in a risk-free manner.